Piece-Rate Incentives and Idea Generation – An Experimental Analysis - Katharina Laske; Nathalie Römer; Marina Schröder (CESifo GmbH, 2024)
We introduce the word illustration task (WIT), a novel experimental task to quantify performance in an idea generation context. Between treatments, we vary whether or not piece-rate (PR) incentives are implemented and the degree to which these incentives are aligned with the desirable outcome. We show that PR incentives have a positive impact on the number of innovative ideas, i.e., the number of ideas that are of high quality and original. We find that unweighted PR incentives (PR provided for any idea) perform at least as well as more aligned weighted PR incentives that are additionally contingent on the quality and/or originality of ideas. Our results suggest that when it comes to fostering idea generation, it is sufficient to incentivize trying instead of incentivizing succeeding.
Keywords: C90; J33; M52; O31; 330; idea generation; real-effort experiment; incentives; creativity